STYLISTIC ANALYSIS ON WALTER SAVAGE LANDOR’S ‘ACON AND RHODOPE; OR, INCONSTANTLY’ - Umi Kulsum (Journal of English Education Program (JEEP), 2021)
This descriptive study is aimed to find out the types and the functions of imagery and to figure out the examples and the functions of archaic words which are found in poem. The documentary data was used in form of poem script “Acon and Rhodope; or, Inconstantly” written by Walter Savage Landor. Content analysis was used by the writer to analyze the content of poem which was adapted from Cohen, et al. (2007, p. 475). The findings showed that there were 174 words or expressions found in poem which were divided into seven types of imagery such as: visual, auditory, gustatory, olfactory, tactile, thermal, and kinesthesia. There were also seven functions of imagery in the poem: 1) visual imagery representing the sense of sight; 2) auditory imagery representing the sense of sound; 3) gustatory imagery or representing the sense of taste; 4) olfactory imagery representing the sense of smell; 5) tactile imagery representing the sense of touch; 6) thermal imagery representing the sense of heat and cold; and 7) kinesthesia imagery appealing to physical sensations of movement, balance, and muscular tension. Also, there were 95 archaic words found in poem to enhance the aesthetical or musical value of the poem, to find out the social life, customs, belief systems and generally cultural richness of the time he emerged, and to make his language old and solemn. It is suggested for the teacher to understand stylistic analysis used by the poets in their poems; and introduce stylistic analysis to the students so that they can improve knowledge of stylistic analysis and understand its meanings. Keywords: archaic words, imagery, stylistic analysis, Walter Savage Landor